The movie star mystery - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (Morton Grove, Ill. : Albert Whitman & Company, 1999)
The Aldens investigate when the arrival of several suspicious characters in Greenfield coincides with a mystery involving a popular boy actor.
540
Accelerated Reader AR
Keywords: Actors and actresses -- Fiction; Brothers and sisters -- Fiction; Orphans -- Fiction; Mystery and detective stories